Phytochemical Composition, Antiradical, Antiproliferative and Antimicrobial Activities of Capsicum frutescens L. - Keser, Serhat; Kaygili, Omer; Keser, Fatma; Tekin, Suat; Yilmaz, Ökkes; Demir, Ersin; Sandal, Suleyman (Taylor and Francis Ltd., 2018)
The pepper fruits keep very important place in the human nutrition and contain some important components in terms of human health. Capsicum frutescens can be consumed both fresh and dry, and has been used in made powdered spices and sauces. In this study, the antiradical activities, phytochemical contents, antimicrobial, antiproliferative activities of water and ethanol extract of C. frutescens fruits were investigated. According to our study results, it was found that the ABTS and OH scavenging activities of C. frutescens extracts are better than the standard antioxidant BHT. It was established that C. frutescens contains high amount of ?-tocopherol, vitamin D, phytosterols, flavonoids, proanthocyanidin, phenolics and unsaturated fatty acids. Also, C. frutescens exhibit very high cytotoxic effects on the MCF-7, HCT-116, LNCaP cancer cell lines. Consequently, these results indicate that cayenne pepper may continue to be consumed by humans owing to it has potentially antioxidant, antiproliferative properties and including bioactive compounds. © 2018 Har Krishan Bhalla & Sons.
Keywords: antimicrobial; C. frutescens; cytotoxic; DPPH?; OH?; phytochemical